2017
DOI: 10.1080/14623943.2017.1323733
|View full text |Cite
|
Sign up to set email alerts
|

Research and reflexivity: the discourse of female students completing teacher education

Abstract: This paper explores the concept of reflexivity and its changing role for both the researcher and participants. A phenomenology was carried out following three female student teachers through their teacher training and how they managed their multiple roles. Twelve semistructured interviews were carried out over the academic year to investigate the changing nature of identity. The discourses of the students were analysed to reveal the equilibrium/ disequilibrium of the student teacher's identity and the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…researcher or teacher educator) not to bring her or his preconceptions into the discussion. This finding was also reported by Meierdirk (2017).…”
Section: Excerpt 2 Groupsupporting
confidence: 88%
“…researcher or teacher educator) not to bring her or his preconceptions into the discussion. This finding was also reported by Meierdirk (2017).…”
Section: Excerpt 2 Groupsupporting
confidence: 88%
“…This WRI loss is represented by the loss of a value or an aspect of a professional identity. The Meierdirk (2017) research into trainee teachers found there was evidence of teachers going through a period of disequilibrium as they discovered the realities of teaching. This was supported by the student-teacher narratives by questioning their own identities and who they were.…”
Section: The Transition From Military To Civilian Lifementioning
confidence: 99%